Upaya Guru Dalam Pembentukan Karakter Anak Usia Dini Melalui Pembiasaan Dan Keteladanan - Rana Manik; Mawaddah Nasution (Multidisciplinary Journal of Religion and Social Sciences, 2025)
Character education for early childhood is a fundamental process in shaping a child's morals, ethics, and personality. The kindergarten stage is considered a golden period where children begin to learn and imitate behaviors from their surrounding environment. Based on observations conducted at RA Aisyiyah Cabang Medan Deli, it was found that character development is highly influenced by the role of teachers. This is because each child has a unique character and personality, so the approach taken by the teacher must be adjusted to the individual needs of each student. This study aims to understand how teachers contribute to shaping children's character through role modeling and habituation. The research uses a qualitative method with data collection techniques such as direct observation and interviews with teachers at the institution. The results indicate that character formation in children is carried out through the habituation of positive behaviors such as honesty, discipline, responsibility, and the ability to cooperate with peers. Teachers' attitudes and behaviors serve as real-life examples for children to imitate. In addition, collaboration between the school and parents plays a crucial role in ensuring that character development is consistent both at school and at home